Modeling and Simulation Study of Reduced Self-Heating in Bottom-Gate β-Ga2O3 MISFETs with a h-BN Gate Insulator - Jo, Sangwook; Yoo, Geonwook; Heo, Junseok (Journal of the Korean Physical Society, 2019)
Beta-gallium oxide (β-Ga2O3) is an emerging ultra-wide bandgap semiconductor material for high-power devices. However, one of the major drawbacks is the low thermal conductivity resulting in poor heat dissipation, and the so-called self-heating effect reduces carrier mobility and drain current degradation, and even causes a device reliability issue. Here, we propose a bottom-gate β-Ga2O3 field-effect transistor with a hexagonal boron-nitride (h-BN) gate-insulator and investigate the self-heating effect in comparison with an aluminum oxide (Al2O3) insulator using physics-based TCAD simulations. The h-BN with high thermal conductivity reduces the lattice temperature of the β-Ga2O3 channel and decreases drain current degradation. Furthermore, as the thickness of the insulator decreases below 50 nm and the channel length is scaled down to 5 μm, the reduced self-heating effect becomes more prominent. The results imply that the highly thermal-conductive h-BN insulator is promising for achieving high performance β-Ga2O3 metal insulator semiconductor field-effect transistor (MISFET) with the bottom-gate configuration.
Keywords: Gallium-oxide; h-BN; Self-heating effect